Review of the state of administrative and procedural regulation in the field of providing administrative services - Markova, O. O.; Маркова, О. О.; ORCID: http://orcid.org/0000-0001-9970-0944 (Європейські перспективи. - 2022. - № 2. – С. 187-193, 2022)
Здійснено огляд адміністративно-процедурного регулювання сфери надання адміністративних послуг крізь призму видів неюрисдикційної адміністративної процедури. В рамках неюрисдикційних процедур розглянуто стан регулювання заявної (дозвільної, реєстраційної) в результаті якої приватним особами надаються адміністративні послуги, а також сформовано пропозиції щодо змісту нормативної конструкції Закону України «Про адміністративну процедуру». Проаналізовано його нормативну конструкцію; зазначено, що вона є придатною лише для адміністративних проваджень, які стосуються прийняття адміністративними органами, в межах реалізації ними дискреційних повноважень, рішень, які обмежують права фізичних чи юридичних осіб або створюють для них додаткові обтяжуючи обов’язки. В той самий час зазначена нормативна конструкція є непридатною для адміністративних проваджень, пов’язаних із наданням адміністративних послуг, які формально мають охоплюватися предметом регулювання даного Закону. Визначено, що положення Закону України «Про адміністративну процедуру» в частині звернення приватних осіб мають поширюватися на надання адміністративних послуг незалежно від сфери. В Законі України «Про адміністративну процедуру» запропоновано присвятити окрему главу адміністративному провадження за зверненнями фізичних чи юридичних осіб в якій прямо закріпити вимоги щодо змісту, форми та реєстрації звернення.

n this article, the author reviews the administrative-procedural regulation of the provision of administrative services through the prism of types of non-jurisdictional administrative procedure. Within the framework of non-jurisdictional procedures, we will consider the state of regulation of the application (permitting, registration), as a result of which a signifi cant number of administrative services are provided by private individuals, and we will also formulate proposals regarding the content of the regulatory structure of the Law of Ukraine «On Administrative Procedure». Having analyzed its normative construction, the author came to the conclusion that it is suitable only for administrative proceedings that concern the adoption by administrative bodies, within the scope of their exercise of discretionary powers, decisions that limit the rights of individuals or legal entities or create additional burdensome obligations for them . At the same time, the specifi ed normative construction is unsuitable for administrative proceedings related to the provision of administrative services, which should formally be covered by the subject of regulation of this Law. The provisions of the Law of Ukraine «On Administrative Procedure» regarding the appeal of private individuals should apply to the provision of administrative services regardless of the area in which they are provided. In the Law of Ukraine «On Administrative Procedure», we propose to devote a separate chapter to administrative proceedings for appeals by individuals or legal entities, in which the requirements regarding the content, form and registration of the appeal are directly established.

Осуществлен обзор административно-процедурного регулирования сферы предоставления административных услуг через призму видов неюрисдикционной административной процедуры. В рамках неюрисдикционных процедур рассмотрено состояние регулирования заявительной (разрешительной, регистрационной), в результате которой частным лицам предоставляются административные услуги, а также сформированы предложения по содержанию нормативной конструкции Закона Украины «Об административной процедуре». Проанализирована его нормативная конструкция; указано, что она пригодна только для административных производств, касающихся принятия административными органами, в рамках реализации ими дискреционных полномочий, решений, ограничивающих права физических или юридических лиц или создающих для них дополнительные отягчающие обязанности. В то же время указанная нормативная конструкция непригодна для административных производств, связанных с предоставлением административных услуг, которые формально должны охватываться предметом регулирования данного Закона. Установлено, что положения Закона Украины «Об административной процедуре» в части обращения частных лиц должны распространяться на предоставление административных услуг независимо от сферы. В Законе Украины «Об административной процедуре» предложено посвятить отдельную главу административному производству за обращениями физических или юридических лиц, в которой прямо закрепить требования по содержанию, форме и регистрации обращения.
Огляд стану адміністративно-процедурного регулювання в сфері надання адміністративних послуг
Markova, O. Review of the state of administrative and procedural regulation in the field of providing administrative services / Markova Olena // Європейські перспективи. - 2022. - № 2. – С. 187-193. - DOI: 10.32782/EP.2022.2.28.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; адміністративно-процедурне регулювання; administrative and procedural regulation; административно-процедурное регулирование; адміністративні процедури; administrative procedures; административные процедуры; законодавство; legislation; законодательство; адміністративне провадження; administrative proceedings; административное производство